Microteaching Mastery: Elevating Postgraduate Medical Training - Tripathi, Santanu Kumar; Samajdar, Shambo S; Chowdhury, Ayona (Bengal physician journal, 2023)
Microteaching, a pedagogical tool initially developed for teacher education, has found its firm foothold in medical education training programs. This narrative review highlights its pivotal role, merits, demerits, and practical implications, particularly in postgraduate evaluations. Emphasizing lesson planning, presentation skills, and effective use of audiovisual aids, microteaching facilitates a deeper understanding of the teaching process and its complexities. Various studies have demonstrated its positive impact on teacher knowledge growth, confidence-bilding, and skill retention, while also promoting problem-solving, critical thinking, and reflective teaching. Beyond the health sciences, it is proven effective in subjects like mathematics. However, challenges persist, with time constraints during sessions and potential administrative bottlenecks when managing large classes. Despite these limitations, the importance of preparing postgraduate candidates for microteaching evaluations is undeniable, requiring a comprehensive understanding and practice of the core skills. The review concludes by advocating for a more widespread adoption and adaptation of microteaching techniques, particularly in regions like India, where its potential remains under-tapped.